HOW TO JUSTIFY AUTOMATION PROJECTS - Velásquez C., José (2004)
This article deals with an Automation Project development. Important aspects with regard to its financial advantages are shown, with the purpose of knowing about the savings engaging a variety of areas within an enterprise, such as security, quality, marketing and logistics.